IMPLEMENTASI FIKIH MUAMALAH DALAM PENGEMBANGAN MEDIA DAKWAH DI ERA MODERN - Isyrokh Fuaidi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2015)
The means and methods of Islamic preaching (dawah) in the modern era have passed through many developments of various aspects. This shows a view that Islam is always relevant and available to meet the needs of the people. This article will explore the relevance of fiqh muamalah as means of dawah in the development of Islamic preachig in the modern world. It can be concluded from the article that fiqh muamalah is a part from the important means and materials that practiced by modern preachers today. This fact is based on the reality that Islamic banking becomes an integral part of the economic system of the world, especially in the countries with a majority Muslim population such as Indonesia. Therefore, as long as there is Islamic economic system and shariah banking in a country, the presence of fiqh muamalah will always become urgent. Furthermore, the relevance of fiqh muamalah in the development of Islamic preaching is elaborated further by discussing the different characteristics of Islamic modern preaching each of which aresupported and generated from the values and principles in jurisprudence muamalah.